Heterogeneous catalyst based on wood substrate loaded cobalt-based metal organic framework as well as preparation method and application of heterogeneous catalyst
By in situ self-assembling a rhombus crystal framework structure loaded with ZIF-67 on wood-derived carbon, the mechanical stability and recyclability problems of cobalt-based metal-organic framework catalysts were solved, achieving efficient and stable catalytic degradation effects, which are suitable for industrial applications.
Patent Information
- Application Number
- CN202510737126.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-04
- Publication Date
- 2025-09-12
AI Technical Summary
Existing cobalt-based metal-organic framework catalysts have deficiencies in mechanical stability, agglomeration and recyclability, resulting in decreased catalytic efficiency and difficulty in large-scale application.
Wood-derived carbon is used as a carrier to form a rhombus crystal framework structure through in situ self-assembly. Combined with Co-OC covalent bond and π-π stacking effect, ZIF-67 is loaded to form a cross-scale mass transfer system, thereby improving mechanical stability and specific surface area.
The catalyst has achieved high efficiency, stability and selectivity, the number of recycling times has been increased from 3 times to 10 times, the degradation efficiency has been maintained above 95%, and the reaction rate constant has reached 1.266min-1, which is suitable for industrial production.
Smart Images

Figure CN120618530A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a heterogeneous catalyst, in particular to a heterogeneous catalyst based on a wood substrate loaded cobalt-based metal organic framework, and also to a preparation method and application of the heterogeneous catalyst. Background Art
[0002] With the acceleration of industrialization, the problem of high-concentration organic wastewater generated during industrial production is becoming increasingly serious. This wastewater contains large amounts of organic pollutants and persistent environmental contaminants, such as antibiotics. Antibiotics (such as norfloxacin, oxytetracycline, and tetracycline) can promote bacterial resistance in the environment even at low concentrations, thereby increasing the selection pressure for drug-resistant bacteria. The presence of these pollutants poses a serious threat to human health and sustainable development.
[0003] Traditional sewage treatment methods can be divided into biological, physical and chemical methods according to different principles. Due to the use of enzymes or biomass, biological methods are expensive, while physical methods have the problem of being unable to completely treat water pollution. Therefore, chemical methods are the most effective wastewater treatment methods in current technology. Based on the heterogeneous catalytic degradation technology of chemical methods, advanced oxidation treatment methods (AOPs) have received widespread attention in the field of organic wastewater treatment. Compared with other chemical methods, AOPs have the characteristics of high oxidation efficiency and no secondary pollution. The advanced oxidation process activates persulfate through a catalyst to produce a variety of active oxidizing species, including sulfate radical anions (·SO42-), hydroxyl radicals (·OH), singlet oxygen ( 1 O2) and superoxide radicals (O 2- ), has the ability to degrade organic pollutants in situ and can effectively eliminate difficult-to-degrade pollutants.
[0004] Metal-organic frameworks (MOFs) are a class of porous materials formed by the self-assembly of metal ions or metal clusters with organic ligands. MOFs possess highly ordered pore structures, high specific surface areas, tunable pore sizes, and chemical functionality, giving them enormous potential for applications in gas storage, separation, and catalysis. ZIF-67, a typical cobalt-based MOF with cobalt ions as the metal center and imidazole ligands as organic linkers, exhibits excellent catalytic performance. Despite its numerous advantages in catalysis, ZIF-67 still faces several challenges in practical applications. ZIF-67 suffers from poor mechanical stability, easy aggregation, and difficulty in recycling, resulting in reduced catalytic efficiency. Existing technologies commonly employ strategies such as core-shell coating or size and morphology manipulation. While core-shell structures inhibit aggregation, the dense shell hinders mass transfer, and differences in thermal expansion coefficients induce interfacial cracking. Size control and particle reduction increase specific surface area but exacerbate van der Waals-driven agglomeration, while residual surfactants block active sites. However, powdered catalysts require complex centrifugal recovery with a low recovery rate. The process is energy-intensive and difficult to scale up, which ultimately leads to a rapid decline in catalytic efficiency with the number of cycles. It is urgent to develop a process with low loss and low energy consumption to produce catalysts with stronger catalytic performance. Summary of the Invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a heterogeneous catalyst based on a wood substrate loaded with a cobalt-based metal-organic framework, which has strong stability, is not easy to agglomerate, and has high degradation efficiency. It also provides a method for preparing the above-mentioned heterogeneous catalyst and its application in the degradation of wastewater containing organic pollutants.
[0006] Technical solution: The heterogeneous catalyst of the present invention is based on a wood substrate loaded with a cobalt-based metal-organic framework, with wood-derived carbon as the carrier. The zeolite imidazolate framework material ZIF67 is loaded on the porous structure surface and interlayer of the carrier, and in situ self-assembles on the inner wall of the wood vessel and between the carbon layers to form a spatially confined rhombus crystal framework structure.
[0007] The mass ratio of the wood to the zeolite imidazolate framework material ZIF67 is 1-1.2:3-3.2.
[0008] The wood-derived carbon is a directionally carbonized natural wood with oxygen-containing functional groups such as hydroxyl and carboxyl groups on its surface. It exhibits a honeycomb-like, interconnected macroporous structure and axially oriented arrangement. During the carbonization process, mesopores and micropores are generated in situ on the tracheid surface, forming a macropore-mesopore-micropore three-level interconnected cross-scale mass transfer system. The wood-derived carbon synergizes with the three-dimensional, continuous graphitized conductive network, achieving lattice-matched anchoring of ZIF67 through Co-OC covalent bonds and π-π stacking effects, while also inducing interfacial electronic reconstruction through Fermi energy differences.
[0009] The method for preparing the above-mentioned heterogeneous catalyst based on wood substrate-supported cobalt-based metal-organic framework comprises the following steps:
[0010] (1) dissolving cobalt nitrate hexahydrate in a methanol solution and mechanically stirring the solution, and then allowing the solution to stand to obtain a homogeneous precursor solution;
[0011] (2) impregnating the wood-derived carbon obtained by wood pretreatment into a homogeneous precursor solution, adding 2-methylimidazole, reacting at room temperature, washing with deionized water, and vacuum drying to obtain an intermediate product;
[0012] (3) The intermediate product is calcined under a nitrogen atmosphere to obtain a heterogeneous catalyst based on a wood substrate supported cobalt-based metal-organic framework.
[0013] Wherein, in step (1), the mass ratio of methanol to cobalt nitrate is 100:1 to 150:1, the mechanical stirring rate is 300 to 500 r / min, the stirring time is 20 to 40 min, and the standing time is 18 to 36 h.
[0014] Wherein, in step (2), the mass of the 2-methylimidazole is 2.2-2.4 g, the drying temperature is 60-80° C., and the drying time is 10-14 h.
[0015] Wherein, in step (2), the pretreatment is to ultrasonically clean the wood with deionized water and ethanol in sequence, then soak it in a mixed solution of NaOH and Na2SO3 to remove lignin and hemicellulose, then calcine it in an inert gas atmosphere, then naturally cool it to room temperature, ultrasonically clean it, and vacuum dry it to obtain wood-derived carbon; specifically, the wood is ultrasonically cleaned with deionized water and ethanol in sequence for 30 to 60 minutes, then soaked in a mixed solution (5wt% NaOH + 2.5wt% Na2SO3, stirred at a constant temperature of 60 to 80°C for 6 to 12 hours) to partially remove lignin and hemicellulose. The chemically pretreated wood is placed in a tube furnace, heated to 600 to 800°C at a heating rate of 5 to 8°C / min under inert gas protection, calcined for 1 to 3 hours, and then naturally cooled to room temperature; the carbonized wood-derived carbon is ultrasonically cleaned and vacuum dried at 60 to 80°C for 12 to 24 hours.
[0016] Wherein, in step (3), the calcination has a heating rate of 4 to 6°C / min, a calcination temperature of 500 to 700°C, and a calcination time of 2.5 to 4.5h.
[0017] The above-mentioned heterogeneous catalyst based on wood substrate-supported cobalt-based metal-organic framework can also be used in the degradation of wastewater containing organic pollutants.
[0018] Wherein, the organic pollutant is norfloxacin (NFX), bisphenol A (BPA), tetracycline (TC) or oxytetracycline (OTC).
[0019] Principle of the invention: The heterogeneous catalyst based on a wood substrate loaded cobalt-based metal-organic framework of the present invention uses the biomass material wood as the catalyst base material, and has the advantages of a porous structure and rich hydroxyl functional groups, rich cellulose, hemicellulose and lignin components, good mechanical properties, renewability and environmental friendliness. By loading ZIF-67 on a wood substrate, not only can the mechanical stability and recyclability of ZIF-67 be improved, but the porous structure of the wood can also be used to increase the specific surface area of the catalyst, thereby improving the catalytic performance. The catalyst can efficiently generate hydroxyl radicals through the synergistic effect of the cobalt-based metal-organic framework and the wood substrate, thereby achieving efficient degradation of organic pollutants.
[0020] This technical solution innovatively transforms the native multi-level pore structure of wood into a cross-scale functional carrier through the concept of biomimetic design. Relying on the honeycomb-like through-hole macropores formed by the directional carbonization of the biomass template and the in-situ growth of the mesoporous-microporous network on the tracheid surface, the confined anchoring growth of ZIF-67 crystals in three-dimensional space is achieved, breaking through the problem of uneven loading caused by the disordered pores of traditional carriers. The continuous graphitized conductive skeleton constructed by lignin carbonization is precisely matched with the lattice parameters of ZIF-67. Combined with the Co-OC covalent bonds between the surface carboxyl / hydroxyl groups and the cobalt nodes and the π-π stacking effect of the carbon layer-imidazole ligand, strong interfacial coupling is established at the atomic scale, which increases the interfacial bonding strength by 3 to 4 times compared with the traditional physical adsorption strategy. The graphitized carbon skeleton forms highly oriented graphite-like crystallites along the growth direction of the wood. The gradient modulus design between ZIF67 and the carbon layer effectively disperses the cyclic stress, so that the catalyst still maintains a high structural integrity under a dynamic pressure of 10 MPa. This synergistic effect stems from the deep integration of cross-scale structural replication of biological templates and atomic-level interface engineering. It breaks through the limitation of "simple addition" of carriers and active components in traditional composite materials, and realizes multi-objective collaborative optimization of mass transfer efficiency-mechanical strength-electron transport-active site density, providing a bionic paradigm for the design of high-performance heterogeneous catalysts.
[0021] The performance of the catalysts is significantly correlated with their structural evolution at different calcination temperatures. The calcination temperature significantly influences the overall performance of the catalyst by regulating the graphitization degree of the carbon support, the stability of the ZIF67 framework, and interfacial interactions. At low temperatures (300-500°C), the carbon support is in a low-graphitization stage, with the ZIF67 framework intact. However, the interface is dominated by weak hydrogen bonding, which limits charge transfer and leads to low catalytic activity and poor cycling stability. When the temperature is increased to 600°C, the carbon layer graphitization is enhanced, and some ZIF67 is partially carbonized to form Co-NC single-atom sites. Simultaneously, the proportion of Co-OC covalent bonds increases, resulting in simultaneous improvements in catalytic activity and stability. However, insufficient mesopore development limits mass transfer efficiency. Calcination at 700°C achieves a synergistic optimization of high specific surface area and moderate graphitization. Partial carbonization of ZIF67 forms Co-NC / open metal site composite active centers. The hierarchical pore system imparts a size-sieving effect, and interfacial covalent bonding and π-π stacking are synergistically enhanced, resulting in peak catalytic activity. After 20 cycles, the activity retention rate is 92%, with high product selectivity. The results show that 700℃ achieves cross-scale synergistic optimization of active site density, electron transport efficiency and mass transfer kinetics by precisely balancing the conductivity of the carbon support, interfacial bonding strength and multi-scale pore matching, becoming the critical temperature point with the best comprehensive performance.
[0022] The present invention establishes a synergistic enhancement mechanism between atomic-level coordination, nanoscale confined growth (directional arrangement of ZIF-67 crystals) and macroscopic fluid channels (directional macropores) through biological template replication and cross-scale interface engineering. In addition, the millimeter-scale block structure can be directly screened and recovered, avoiding the industry pain points of large centrifugal loss and high energy consumption of powder catalysts, and providing a new paradigm for the industrial application of MOFs catalysts that combines bionic intelligence and engineering feasibility.
[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The catalyst of the present invention has a large specific surface area, which is conducive to contact with the substrate and the oxidant. It has extremely strong catalytic degradation performance for wastewater containing difficult-to-degrade organic pollutants such as norfloxacin, bisphenol A, tetracycline and oxytetracycline. At the same time, it also has good selectivity and stability. Compared with the ZIF-67 catalyst, the number of recycling times of the catalyst of the present invention is increased from 3 times to 10 times, the degradation efficiency is maintained at more than 95%, and the reaction rate constant reaches 1.266min -1 , can be recycled multiple times; (2) its preparation method is simple, the reaction conditions are mild, it is environmentally friendly, and it is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1TEM images of ZIF67@WD-700N2 (ad) and ZIF67@WD-700Air (f) of the present invention, and TEM image of wood-derived carbon (e);
[0025] Figure 2 Effects of PMS dosage (a, b), catalyst dosage (c, d), and initial BPA concentration (e, f) on the catalytic degradation of BPA by ZIF67@WD and the first-order kinetic curves; Effects of temperature (g, h) on the catalytic degradation of BPA and the first-order kinetic curves. Reaction conditions: [BPA] = 20 mg·L -1 , [PMS] = 0.2 g·L -1 , [catalyst] = 0.2 g·L -1 , temperature 30℃; corresponding Arrhenius plot: ln(k) vs. T -1 (i);
[0026] Figure 3 Effect of quencher on degradation performance (a); effect of anion on degradation performance (b); effect of different water qualities on degradation performance (c); degradation ability of catalyst for different pollutants (d); total organic carbon (TOC) degradation curves of different pollutants (e) and cycle test (f). Reaction conditions: [BPA] = 20 mg·L -1 , [PMS] = 0.2 g·L -1 , [catalyst] = 0.2 g·L -1 , temperature 30℃. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further described below with reference to the examples. The test materials used in the examples can all be purchased through conventional channels.
[0028] Example 1
[0029] The present invention is based on a wood substrate-supported cobalt-based metal-organic framework heterogeneous catalyst, and its preparation method comprises the following steps:
[0030] (1) Dissolve 0.668 g of cobalt nitrate hexahydrate in 100 mL of methanol, stir mechanically at 400 rpm for 30 min, and let stand for 24 h to form a homogeneous precursor solution;
[0031] (2) The pretreated wood was immersed in the homogenized precursor solution. After a period of immersion, 2.242 g of 2-methylimidazole was added and reacted at room temperature for 12 h. After washing with deionized water, the wood was vacuum dried at 70 °C for 12 h.
[0032] (3) The material obtained in step 2 was placed in a tubular furnace, heated to 500°C at 5°C / min under a nitrogen atmosphere, and calcined for 3 h to obtain ZIF67@WD-500.
[0033] Example 2
[0034] The present invention is based on a wood substrate-supported cobalt-based metal-organic framework heterogeneous catalyst, and its preparation method comprises the following steps:
[0035] (1) Dissolve 0.668 g of cobalt nitrate hexahydrate in 100 mL of methanol, stir mechanically at 400 rpm for 30 min, and let stand for 24 h to form a homogeneous precursor solution;
[0036] (2) The pretreated wood was immersed in the homogenized precursor solution. After a period of immersion, 2.242 g of 2-methylimidazole was added and reacted at room temperature for 12 h. After washing with deionized water, the wood was vacuum dried at 70 °C for 12 h.
[0037] (3) The material obtained in step 2 was placed in a tubular furnace, heated to 600°C at 5°C / min under a nitrogen atmosphere, and calcined for 3 h to obtain ZIF67@WD-600.
[0038] Example 3
[0039] The present invention is based on a wood substrate-supported cobalt-based metal-organic framework heterogeneous catalyst, and its preparation method comprises the following steps:
[0040] (1) Dissolve 0.668 g of cobalt nitrate hexahydrate in 100 mL of methanol, stir mechanically at 400 rpm for 30 min, and let stand for 24 h to form a homogeneous precursor solution;
[0041] (2) The pretreated wood was immersed in the homogenized precursor solution. After a period of immersion, 2.242 g of 2-methylimidazole was added and reacted at room temperature for 12 h. After washing with deionized water, the wood was vacuum dried at 70 °C for 12 h.
[0042] (3) The material obtained in step 2 was placed in a tubular furnace, heated to 700 °C at 5 °C / min under a nitrogen atmosphere, and calcined for 3 h to obtain ZIF67@WD-700N2.
[0043] Comparative Example 1
[0044] A catalyst, compared with Example 2, wherein the calcination atmosphere is changed to air, and the preparation method thereof comprises the following steps:
[0045] (1) Dissolve 0.668 g of cobalt nitrate hexahydrate in 100 mL of methanol, stir mechanically at 400 rpm for 30 min, and let stand for 24 h to form a homogeneous precursor solution;
[0046] (2) The pretreated wood was immersed in the homogenized precursor solution. After a period of immersion, 2.242 g of 2-methylimidazole was added and reacted at room temperature for 12 h. After washing with deionized water, the wood was vacuum dried at 70 °C for 12 h.
[0047] (3) The material obtained in step 2 was placed in a tube furnace, heated to 700°C at a rate of 5°C / min under air atmosphere, and calcined for 3 h to obtain ZIF67@WD-700Air.
[0048] Structural exploration of the heterogeneous catalysts prepared in the examples:
[0049] like Figure 1 Shown are TEM images of ZIF67@WD-700N2 (ad) and ZIF67@WD-700Air (f), and TEM image of wood-derived carbon (e). Figure 1 (ad) It can be seen that under nitrogen atmosphere, the particles are in the form of micrometer-scale particles and are evenly attached to the surface of the wood substrate, indicating a high dispersion loading process. Figure 1 (e) It can be seen that the wood-derived carbon completely retains the directional honeycomb porous structure of natural wood, forming through-hole macroporous channels and forming a hierarchical porous system. Figure 1 (f) It can be seen that in the air atmosphere, particles are densely accumulated at the edges of the cracks in the wood trunk, which may be related to the fluid dynamic characteristics in the cracks.
[0050] The catalytic performance of the heterogeneous catalysts prepared in the examples was investigated:
[0051] like Figure 2 As shown, the effects of PMS dosage (a, b), catalyst dosage (c, d), and initial BPA concentration (e, f) on the catalytic degradation of BPA by ZIF67@WD and the first-order kinetic curves; the effects of temperature (g, h) on the catalytic degradation of BPA and the first-order kinetic curves, reaction conditions: [BPA] = 20 mg·L -1 , [PMS] = 0.2 g·L -1 , [catalyst] = 0.2 g·L -1 , temperature 30℃; corresponding Arrhenius plot: ln(k) vs. T -1 (i).
[0052] Catalytic performance test experiment:
[0053] A certain amount of PMS was added to a BPA solution with an initial concentration of 20 mg·L-1, and the initial concentration before the addition of the catalyst was recorded using an ultraviolet spectrophotometer. Subsequently, ZIF67@WD-700N2 was dispersed in the BPA solution, and then the PMS solution was added at certain intervals. The BPA solution concentration was determined by separating the catalyst from the mixed solution at certain intervals using an aqueous filter membrane (0.45 μm) and performing UV spectrophotometry detection. The reaction parameters were optimized through control experiments with different catalyst concentrations, PMS concentrations, and BPA concentrations. With other conditions unchanged, degradation experiments of different pollutants (NFX, TC, OTC) were carried out according to the optimized reaction parameters. In addition, in order to explore the reaction mechanism of BPA degradation under optimal conditions, free radical quenching experiments were carried out using different free radical quenchers. The initial concentration is C0, and the real-time concentration of the pollutant is C t , t (min) is the reaction time, and the kinetic parameter ln (C t / C0)=-kt, and obtain the degradation curve of pollutants changing with time to evaluate the degradation performance of the catalyst.
[0054] Figure 2 Figures a and b show the BPA degradation curves and fitted reaction kinetics curves obtained by varying the PMS dosage alone. Increasing the PMS dosage increases the number of active sites and the degradation rate, leading to complete BPA degradation in approximately 5 minutes. Excessive PMS may over-adsorb on the catalyst, weakening the activation effect and inhibiting activation. Therefore, the optimal PMS dosage is 0.2 g·L. -1 . Figure 2 Figures c and d show that, when other conditions remain unchanged and only the catalyst dosage is changed, increasing the catalyst dosage increases the number of active sites in contact with pollutants and significantly increases the reaction rate. However, excessive catalyst is useless in increasing the degradation rate. Taking into account the raw material cost, the catalyst dosage is determined to be 0.2 g·L -1 For the best process conditions. Figure 2 Figures e and f show that the catalytic degradation performance decreases with the increase of the pollutant BPA concentration, and the catalyst and PMS can play a better role at low BPA concentration. Figure 2 The effect of temperature on the degradation performance was investigated in GI. The degradation rate increased with increasing temperature. The activation energy Ea was calculated using the Arrhenius equation to be 9.378 kJ mol -1 This value offers significant advantages in the catalyst-activated PMS degradation of BPA. At the same temperature, it can increase the reaction rate constant, accelerate the reaction rate, and improve wastewater treatment efficiency. It also reduces the reaction temperature requirement, conserves energy, and facilitates the application and promotion of industrial-scale wastewater treatment processes.
[0055] like Figure 3 Figure 2 shows the effect of quencher on degradation performance (a); the effect of anions on degradation performance (b); the effect of different water qualities on degradation performance (c); the degradation ability of the catalyst for different pollutants (d); and the total organic carbon (TOC) degradation curves of different pollutants (e) and cycle tests (f). Reaction conditions: [BPA] = 20 mg·L -1 , [PMS] = 0.2 g·L -1 , [catalyst] = 0.2 g·L -1 , temperature 30℃.
[0056] In order to study the reactive oxygen species (ROS) in the degradation process of BPA by ZIF67@WD-700N2, four quenchers, namely methanol (MeOH), tert-butyl alcohol (TBA), histidine (L-his) and p-benzoquinone (p-BQ), were added to explore the ROS that played a major role in the degradation process through the quenching effect. MeOH can quench ·OH and ·SO4, TBA is mainly used to quench ·OH. L-his and p-BQ can be used as 1 O2 and O 2- Quencher. Figure 3 As shown in Figure a, after adding the quencher, the BPA degradation rate decreased to varying degrees. Among them, after adding L-his and p-BQ quenchers, the BPA degradation rate decreased significantly. 1 O2 and O 2- It is the main active substance and plays an important role in the catalytic degradation of pollutants.
[0057] In order to investigate the effect of inorganic anions in the environment on the catalytic degradation of bisphenol A, the effects of different inorganic anions on the catalytic degradation of bisphenol A by ZIF67@WD-700N2 were investigated. Figure 3 (b) shows the experimental results after adding different anions under the optimal experimental conditions. The results show that the inhibitory effect of the studied anions on BPA degradation is from large to small. 2- >HCO3 - >H2 PO4 - >Cl - >SO4 - .
[0058] Figure 3 Panel (c) shows the catalyst's water treatment and recovery performance testing results in tap water and lake water. As shown, BPA is highly degraded in tap water, completely degrading within 5 minutes. However, due to the high concentration of inorganic ions and total organic carbon in lake water, the degradation rate in lake water is somewhat lower, but still exceeds 80%.
[0059] In order to verify that ZIF67@WD-700N2 has good degradation performance on BPA and antibiotics produced by degradable plastics, PBA conducted antibiotic degradation experiments. Figure 3 Middle (d) is an antibiotic degradation experiment. The results show that ZIF67@WD-700N2 exhibits high catalytic activity in the catalytic degradation of tetracycline and oxytetracycline, and can completely degrade OTC and TC within 3 minutes.
[0060] During the catalytic degradation process, organic macromolecules are decomposed into small molecules, but these small molecules are potentially toxic or even more toxic. Therefore, the TOC of the organic matter degradation process is measured to determine the effect of organic matter mineralization. Figure 3 As shown in (e). Compared with other organic pollutants, TOC removal of NFX is the most difficult. In summary, ZIF67@WD-700N2 shows good application potential in the field of catalytic degradation of organic pollutants.
[0061] The stability of the catalyst was tested by catalytic degradation cycle experiments of BPA. Figure 3 As shown in (f), the performance of the catalyst decreased slightly after the cycle, which may be due to the high carbon content in the catalyst and the partial loss of activity of the metal active centers after the reaction. However, the catalyst still showed high activity after several cycles. This shows that the catalyst has good reusability in practical applications.
Claims
1. A heterogeneous catalyst based on a wood substrate supported cobalt-based metal-organic framework, characterized in that: The heterogeneous catalyst uses wood-derived carbon as a carrier, and the zeolite imidazolate framework material ZIF67 is loaded on the porous structure surface and interlayer of the carrier, and in-situ self-assembles on the inner wall of the wood vessel and between the carbon layers to form a rhombus crystal framework structure.
2. The heterogeneous catalyst according to claim 1, characterized in that The mass ratio of the wood-derived carbon to the zeolite imidazolate framework material ZIF67 is 1-1.2:3-3.
2.
3. The heterogeneous catalyst according to claim 1, characterized in that The wood-derived carbon is directionally carbonized natural wood with oxygen-containing functional groups on the surface, a honeycomb-like through-hole macroporous structure and an axially oriented arrangement. At the same time, during the carbonization process, mesopores and micropores are in situ generated on the surface of the tracheids, forming a cross-scale mass transfer system with three-level interconnection of macropores, mesopores and micropores.
4. A method for preparing a wood substrate-supported cobalt-based metal-organic framework heterogeneous catalyst according to claim 1, characterized in that: The following steps are involved: (1) dissolving cobalt nitrate hexahydrate in a methanol solution and mechanically stirring the solution, and then allowing the solution to stand to obtain a homogeneous precursor solution; (2) impregnating the wood-derived carbon obtained by wood pretreatment into a homogeneous precursor solution, adding 2-methylimidazole, reacting at room temperature, washing with deionized water, and vacuum drying to obtain an intermediate product; (3) The intermediate product is calcined under a nitrogen atmosphere to obtain a heterogeneous catalyst based on a wood substrate supported cobalt-based metal-organic framework.
5. The method according to claim 4, characterized in that: In step (1), the mass ratio of methanol to cobalt nitrate is 100:1 to 150:1, the mechanical stirring rate is 300 to 500 r / min, the stirring time is 20 to 40 min, and the standing time is 18 to 36 h.
6. The method according to claim 4, characterized in that: In step (2), the mass of the 2-methylimidazole is 2.2 to 2.42 g, the drying temperature is 60 to 80° C., and the drying time is 10 to 18 h.
7. The method according to claim 4, characterized in that: In step (2), the pretreatment is to sequentially clean the wood with deionized water and ethanol ultrasonically, then immerse it in a mixed solution of NaOH and Na2SO3, remove lignin and hemicellulose, calcine it in an inert gas, and then naturally cool it to room temperature, ultrasonically clean it, and vacuum dry it to obtain wood-derived carbon.
8. The method according to claim 4, characterized in that: In step (3), the calcination has a heating rate of 4 to 6°C / min, a calcination temperature of 500 to 700°C, and a calcination time of 2 to 4 hours.
9. Use of the wood substrate-supported cobalt-based metal-organic framework heterogeneous catalyst according to claim 1 in the degradation of wastewater containing organic pollutants.
10. The use according to claim 9, characterized in that The organic pollutants are norfloxacin, bisphenol A, tetracycline or oxytetracycline.